An examination of the effects of family, school, and community resilience on high school students’ resilience in China - Qi, Chunlin; Yang, Nanchang (Frontiers in Psychology, 2024)
Introduction Resilience plays a pivotal role in shaping the academic accomplishments, psychological well-being, and future prospects of high school students. Despite its significance, there is a notable dearth of studies examining the current state and determinants of resilience among high school students in China. Methods This research addresses this gap by assessing and exploring levels of resilience and their interconnections across four key domains—individual, family, school, and community—among Chinese high school students. The study also investigates variations in resilience based on factors such as gender, geographical location, and grade levels. A total of 667 high school students participated in the study, responding to four resilience scales. Results Chinese high school students exhibited generally low levels of resilience, with family resilience ranking the highest and community resilience the lowest. The study revealed that resilience is positively influenced by resilience levels in school, family, and community settings. Consequently, strategies aimed at fortifying resilience should prioritize interventions in familial, educational, and communal environments. Discussion Moreover, the research findings indicate noteworthy disparities in resilience among high school students based on gender, urban-rural divide, and grade levels. Female, urban, and lower-grade students displayed higher resilience compared to their male, rural, and higher-grade counterparts. This highlights the importance of focusing on resilience-building measures tailored to male, rural, and higher-grade high school students, given their increased likelihood of facing significant challenges and stressors in both academic and personal spheres. Conclusion This study contributes to the broader understanding of resilience by investigating the correlations between individual, family, school, and community resilience among Chinese high school students. The findings underscore the need for targeted interventions to enhance resilience, particularly in specific demographic groups, thereby advancing the efficacy of resilience-building techniques in high school settings.